Surviving the Arab uprisings: Political regimes and state responses - Ahmed, Hood (AUC Knowledge Fountain, 2018)
The Arab uprisings threatened authoritarian states across the Arab world with unprecedented levels of mobilization. The nature of these challenges, the states’ responses and the outcomes have been, however, markedly uneven. In accounting for this divergence, while some approaches have examined the structural preconditions for transitions, others have emphasized the impact of interactions between different political actors. This thesis draws on both approaches through examining how the state’s institutional structure shapes the opportunities and constraints of states in employing different authoritarian strategies. It examines why and how different regimes have used different authoritarian strategies to survive and stabilize. In responding to threats of instability, some states use measures of legitimation through concessions and accommodations, others use measures of cooptation through including strategic actors into the regime elite, while some resort to repression, whether through physical violence or restrictions of political and civil rights. The thesis uses Michael Herb’s regime typology and uses Saudi Arabia, Morocco and Egypt as its cases to examine how different institutional structures reinforce the choice of strategy. Through comparing state responses across cases and across time for each case, the thesis explains how authoritarian strategies vary across different regimes and across time for each regime. The thesis concludes by analyzing the costs and benefits of different authoritarian strategies and how they contribute to different patterns of stability.